Commercial Probiotic Drink and Sumbawa Horse Milk as Lactic Acid Bacteria Source for Virgin Coconut Oil Extraction - Chaidir, Riri Rimbun Anggih; Suharli, Lili; Yasdia, Rahmi (Universitas Al Azhar Indonesia, 2023)
Virgin coconut oil (VCO) can be produced without heat, without any alteration, requires minimal investments and energy during production, and has been reported to have many health benefits. We produced VCO with the addition of lactic acid bacteria (LAB) sources with combined method of chilling-thawing and fermentation. The LAB sources used were Sumbawa horse milk (SKL) and commercial probiotic milk (SPK). This study used a completely randomized design (CRD) using both LAB sources which were added to coconut milk, respectively 10 ml, 12.5 ml and 15 ml and compared with control or no treatment. LAB were also isolated from blondo and VCO using LAB specific medium, MRSA. The extracted VCO has the characteristics of clear color with a distinctive coconut smell and long shelf-life. Three LAB isolates were obtained, VCO1-3. VCO1 was found in all samples, with colony morphology of circular and entire margin, convex surface, small in size, and white in color. SKL10, SKL15 and SPK10 showed significant difference to the control, with VCO yield of 31.49-33.05 %, significantly higher than that of without LAB treatment. Both LAB sources of single (SPK) and mixed inoculums (SKL) showed higher yields, indicated their potential as starter for VCO extraction.Keywords - Virgin Coconut Oil, VCO, Chilling-Thawing Extraction, Fermentation Extraction, Cold Pressed Oil, Lactic Acid Bacteria.